DRUMBAND LEARNING FOR CHILDREN OF GROUP B IN TK MARSUDIRINI KANAK-KANAK JESUS SEMARANG CITY - Hidayat, Aditya Fitria Maulana; Nugroho, Agustinus Arum Eka (Jurusan PGPAUD FIP UNNES, 2019)
This research is conducted to analyze and encourage the process of drumband learning in group B children at TK Marsudirini Kanak-Kanak Jesus Semarang City. This study uses a qualitative method with a descriptive approach. The study is conducted at the TK Marsudirini Kanak-Kanak Jesus Semarang City. The research subjects used as data sources are the principal, the drumband assistant teacher, and the TK drumband trainer. Data collection techniques are observation, interviews, and documentation. The data are analyzed using data reduction, data presentation, and conclusion drawing. The results of the study showed that drumband learning at TK Marsudirini Kanak-Kanak Jesus Semarang City is held every Wednesday by bringing one trainer from outside the school. The trainer uses lecture learning methods and demonstration methods. The difference that exists with other TK is the implementation of learning carried out in school hours, the rest of the drumband activities are the same as other schools. Children only follow the instructor?s instructions during the activity, and the drumband activities have been prepared by the teacher to fill the Christmas celebration held by the school.